Rotor position estimation over entire speed range of interior permanent magnet synchronous motors - Lee, Hyung Woo; Cho, Dae Hyun; Lee, Kyo Beum (Journal of Power Electronics, 2021)
This paper presents a method for transitioning between sensorless rotor position estimation methods for an interior permanent magnet synchronous motor (IPMSM). Through the proposed method, rotor position estimation over the entire speed range of the IPMSM is possible. Considering that each sensorless method governs a different speed range for estimating rotor position and speed with good accuracy, a strategy for transitioning between two methods is indispensable. In this study, a sensorless method based on extended back electromotive force (EMF) is used for high-speed operation. In addition, during low-speed operation, rotor position is estimated using the slope of measured current through the application of a zero-voltage vector. A weight function is applied to the position and speed information obtained from the two sensorless methods. The combined information is then used throughout the speed range of the IPMSM. To achieve smooth transitions, the weight function is altered based on the rotor speed in the transition region. The effectiveness of the proposed transition method was demonstrated via simulations and experiments.
Keywords: Back electromotive force; Combined informations; High-speed operation; Interior permanent magnet synchronous motor; Low speed operation; Rotor position estimation; Smooth transitions; Zero voltage vectors; Extended electromotive force; Interior permanent magnet synchronous motor; Sensorless control; Transition method; Zero-voltage vector